Design and analysis of equal power divider using 4-branch waveguide - Yik Seng , Yong; Low, A.L.Y.; Su Fong , Chien; Ah Heng , You; Hin-Yong , Wong; Yee Kit , Chan (2005)
A numerical model of an equal power divider based on the 4-branch single-mode waveguide is proposed. This proposed design does not require extra fabrication process and supplementary structure modification compared to other typical multibranch waveguides. The condition of uniform output power distribution can be easily obtained by adjusting the branching angle between the inner and the outer branches without introducing excess scattering loss. Similar design procedures can also be used when other power dividing ratios or operating wavelengths are specified. In our study, all the four output ports' power is uniform for both TE and TM mode within a difference of less than 0.1 dB. The bandwidth with an output power dividing ratio variation value smaller than 0.3 dB is found to be nearly 350 angstrom, which is sufficient for wavelength division multiplexing systems where erbium-doped fiber amplifiers are used.